Mathematical modeling and analysis of dynamic behaviour of a fed-batch penicilin G fermentation process - Ahmad, Arshad; Abdul Samad, Nor Asma Fazli; Chow, Ai Wei (Universiti Malaysia Sabah, 2003)
This paper discusses the characteristics of penicilin G fermentations with substrate inhibition using dynamic simulations. The fermentation process was simulated in MATLAB environment and analyses of the dynamic behaviour of the process were carried out to provide the necessary process insights. Dynamic simulations revealed variations in the sensitivity of the model to substrate concentrations, depending on the operating point. This variation indicates non-linearity in dynamic behaviour. PID control was also evaluated and results are demonstrated.